Development of Student Worksheets Based on React Model to Increase Student Motivation in Newton's Law Materials - Muhammad Ichsan; Yusrizal Yusrizal; Mursal Mursal (Postgraduate, University of Mataram, 2021)
The purpose of this study was to determine the feasibility of student worksheets based on the REACT model in increasing motivation on Newton's law material at the Aceh Aviation State Vocational High School. This study uses research and development methods with the ADDIE model. The results obtained are the average value of the validator's assessment shows a value of 87.3% with a very decent category, as well as the results of the gain classification to see an increase in student motivation of 0.61 which is in the medium category. It was concluded that the developed student worksheet based on the REACT model was feasible to use and could increase students' motivation on Newton's law material at the Aceh Aviation State Vocational High School